Pan-RNA editing analysis of the bovine genome. Issue 3 (4th March 2021) - Cai, Wentao; Shi, Lijun; Cao, Mingyue; Shen, Dan; Li, Junya; Zhang, Shengli; Song, Jiuzhou
ABSTRACT: RNA editing is an essential process for modifying nucleotides at specific RNA sites during post-transcription in many species. However, its genomic landscape and characters have not been systematically explored in the bovine genome. In the present study, we characterized global RNA editing profiles from 50 samples of cattle and revealed a range of RNA editing profiles in different tissues. Most editing sites were significantly enriched in specific BovB-derived SINEs, especially the dispersed Bov-tAs, which likely forms dsRNA structures similar to the primate-specific Alu elements. Interestingly, ADARB1 (ADAR2) was observed to be predominant in determining global editing in the bovine genome. Common RNA editing sites among similar tissues were associated with tissue-specific biological functions. Taken together, the wide distribution of RNA editing sites and their tissue-specific characters implied the bovine RNA editome should be further explored.